The Effectiveness of Five Finger Hypnosis and Deep Breathing Relaxation on Anxiety Before Childbirth in Pregnant Women in the Third Trimester - Lastiar Simamora; Palupi, Retno; Nining Istighosah; Erma Retnaningtyas (Universitas STRADA Indonesia, 2025)
One of the health problems in Indonesia is the anxiety of pregnant women before giving birth in the third trimester. The aim of the research was to analyze the effect of five finger hypnosis and deep breathing relaxation on anxiety before childbirth in third trimester pregnant women at the Sandul Community Health Center. The research design is quantitative observational with two group pre test and post test approach with the research focus directed at analyzing the effect of five finger hypnosis and deep breathing relaxation on anxiety before delivery in third trimester pregnant women at the Sandul Community Health Center. The population in the study was 66 respondents and the sample was 60 respondents taken using the Accidental Sampling technique. The research results showed that almost half of the respondents before being given five-finger hypnosis had moderate anxiety. After being given five-finger hypnosis, anxiety fell into the low category at 36.7%. Meanwhile, almost half of the respondents before being given deep breathing relaxation had moderate anxiety. After being given deep breathing relaxation, anxiety became the low category at 40.0%. Based on the results of the Paired t test analysis, the results were obtained p-value is 0.002 < 0.05, so H0 is rejected and H1 is accepted, so it is concluded that there is an influence of five finger hypnosis on anxiety before childbirth in third trimester pregnant women at the Sandul Community Health Center. Based on the results of the Paired t test analysis, the results were obtained p-value is 0.040 < 0.05, so H0 is rejected and H1 is accepted, so it is concluded that there is an influence of deep breathing relaxation on anxiety before childbirth in third trimester pregnant women at the Sandul Community Health Center. By fully involving themselves, pregnant women can optimize the benefits of these two techniques in managing anxiety before giving birth.